Significance of the isolation of Clostridium welchii from routine blood cultures. - Ahmad, F J (1976)
Clostridium welchii has been demonstrated in approximately 20% of contact plates taken from the antecubital fossa of 185 inpatients and outpatients and healthy staff. The highest incidence was in a group of 40 very ill patients. The isolation of the organism from blood cultures is not always of clinical significance. Skin preparation as at present practised is often inadequate to remove the spores when contamination is relatively heavy, for example, in bedridden patients.